Quality of life in epilepsy: comparison between Indonesian version of QOLIE-10 and QOLIE-31 - Mirawati, Diah Kurnia; Handayani, Lestari; Subandi, Subandi; Hafizhan, Muhammad; Putra, Stefanus Erdana (Intelektual Pustaka Media Utama, 2023)
Quality of Life in Epilepsy Inventory 10 (QOLIE-10) and QOLIE-31 is used to measure patient’s quality of life. While longer version of QOLIE-31 is thought to have higher validity and reliability, QOLIE-10 is shorter and more practical to use in clinical setting. This study aimed to compare Indonesian version of QOLIE-10 and QOLIE-31. This was a cross sectional study conducted at Dr. Moewardi General Hospital, Surakarta, Indonesia. Participant were asked to complete the Indonesian version of QOLIE-10 and QOLIE-31, and data obtained then analysed to find the correlation between QOLIE-10 and QOLIE-31. A total of 51 epilepsy patients were included on this study. We observed correlation of 0.41 to 0.84 (p<0.05) for each item of QOLIE-10 with their respective QOLIE-31 subscale. We also found correlation value of 0.898 (p=.000) between total score of QOLIE-10 and QOLIE-31 showing strong positive correlation of two questionnaire. Independent T-sample test on QOLIE-10 and QOLIE-31 T-score result of p=.361, showing no statistical difference between two questionnaires. Frequency of seizure is correlated with patients’ quality of life. QOLIE-10 has strong positive correlation to QOLIE-31, which make it a useful tool to assess epilepsy patients’ quality of life.